"Stuck in the middle" first-line healthcare managers' responsibilities and needs of support when applying Lean. Issue 2 (4th May 2020) - Kahm, Therese; Ingelsson, Pernilla
Abstract : Purpose: The purpose of this paper is to present the supportive conditions that the first-line health-care managers claim that they need from their own managers and what they experience as their own roles and responsibilities in relation to their coworkers when applying Lean principles and practices. Design/methodology/approach: A survey with a Web-based questionnaire was designed and used in a Swedish health-care organization two years after the initiation of Lean to investigate the managers' views on their role, conditions and ability to create change according to Lean. The result from two of the questions will be presented where one focuses on the relationship to the first-line managers' own manager and the second on the relationship to their coworkers. Findings: The results show that to initiate improvement, work based on Lean first-line managers ask for own managers who are assured about Lean, include them in discussions and ask for follow-ups and results about Lean. Concerning first-line managers' relation to their coworkers they experience themselves as responsible for leading toward creating a culture where problems and mistakes are viewed as possibilities to improve, for encouraging that new work procedures are tested and for creating commitment and inspiration in relation to their coworkers. Originality/value: The questions can be used separately or as part of an entire questionnaire before and along the Lean process to highlight organizational issues such as shared responsibility and supportive relations when developing health care.